Comparison of the macroscale and microscale tests for measuring elastic properties of polydimethylsiloxane. Issue 42 (23rd July 2015) - Sharfeddin, Asma; Volinsky, Alex A.; Mohan, Greeshma; Gallant, Nathan D.
ABSTRACT Polydimethylsiloxane (PDMS) has many biomedical applications, since it is biocompatible, easy to fabricate and inexpensive. The response of biological cells and tissues is affected by the mechanical properties of the PDMS surface, which can be controlled by varying the crosslinking percentage. It is essential to find reliable ways to measure elastic properties of PDMS prepared with different surface conditions or stiffness gradients. In this paper, the elastic modulus of PDMS was measured at different scales as a function of the crosslinking percentage varied from 2% to 9%. Macroscopic compression and tension tests were used and compared with the nano‐JKR (Johnson‐Kendall‐Roberts) method applied to a microindentation test. Depending on the test, the PDMS elastic modulus increased from 10 to 85 fold with the crosslinking percentage change from 2% to 9%. The PDMS elastic modulus varied as a sigmoid function with the crosslinking percentage for each type of test. The compression macroscale test is the easiest way to estimate the elastic modulus of stiffer PDMS with higher crosslinking percentage. For the more compliant and tacky PDMS samples with lower crosslinking percentage the nano‐JKR test is more suitable, as it is sensitive and accounts for the surface adhesion forces. The samples with the lower crosslinking percentage are much less stiff in tension than in compression, resembling liquid‐like behavior. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42680.